KAFĀ’AH AS THE BASIS FOR PROHIBITING INTERFAITH MARRIAGE IN THE COMPILATION OF ISLAMIC LAW: A CONTEMPORARY ANALYSIS OF MAQĀṢID AL-USRAH - Elyas Desima Saputra; Ermanita Permatasari; Mahfud (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - Interfaith marriages among Muslims in Indonesia are becoming increasingly common. These marriages are legally conducted by exploiting the dualism of interpretation of interfaith marriage laws in the Marriage Law. Amidst this debate, the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) redefined the concept of kafā’ah as the absolute basis for prohibiting interfaith marriages. This provision is one of the efforts to maintain the welfare of marriage that is relevant to the spirit of maqāṣid al-Usrah. This study aims to analyze the repositioning of the concept of kafā’ah as the basis for prohibiting interfaith marriage in the KHI using a contemporary analysis of maqāṣid al-usrah. Method - This qualitative study used library research methods and was descriptive-analytical in nature. The primary data in this study is the KHI, especially the articles that discuss kafā’ah. Secondary data were obtained from the Marriage Law and various scientific literature relevant to the research theme. Data were collected through documentation techniques and analyzed using content analysis techniques. Findings - The results of the study show that the KHI explicitly places religious similarity as a fundamental and absolute criterion of kafā’ah, as stated in Article 40 letter c and Article 44 of the KHI, which prohibits marriage between Muslims and non-Muslims. Originality/Value – The basis for this prohibition is reinforced by the analysis of maqāṣid al-usrah, especially in maintaining ḥifẓ al-dīn (protection of religion) and ḥifẓ al-nasl (protection of offspring). Religious differences are seen as having the potential to cause ideological disorientation, conflicts in the education of children, and complications in inheritance law, all of which threaten the integrity and harmony of Muslim families. This prohibition is a preventive measure by the KHI to protect the interests of Muslims and ensure the creation of harmonious families based on Islamic laws. Contribution/Limitation of Research – This study contributes to the theoretical development of Islamic family law thinking and knowledge, particularly in terms of legislative studies and family welfare values in the contemporary context. However, this study is still limited to normative analysis through documentary studies of the KHI.